Investigation of the discrimination and characterization of blood serum structure in patients with opioid use disorder using IR spectroscopy and PCA-LDA analysis - GÜNDÜZ, OĞUZHAN (ELSEVIER, 2020)
Harmful illicit drug use, such as opioid use disorder (OUD), causes multiple diseases that result in physiological, pathological, and structural changes in serum biochemical parameters based on the period of use. Fourier-transform infrared (FTIR) spectrometry is a noninvasive optical technique that can provide accurate evidence about the biochemical compounds of analytical samples. This technique is based on the detection of functional groups and the spectral analysis of the region of the selected bands, which provides a reliable and accurate tool for evaluating changes in the biochemical parameters of OUD patients. In the present study, the Attenuated Total Reflection (ATR)-FTIR technique and clinical laboratory biochemical results were used to investigate the phospholipid-protein balance in the blood serum of participants with OUD by comparing their data to that of healthy controls. To compare the biochemical laboratory results with serum vibrational spectroscopy, we used infrared (IR) spectroscopy to distinguish the serum of the OUD patients, who had an average duration of use of 7.31 +/- 3.8 years (ranging from 6 to 15 years). We aimed to compare the clinical reports with findings from IR spectroscopy coupled with chemometrics analysis, principal component analysis (PCA), and linear discriminant analysis (LDA). The serum samples of the OUD male patients (n = 20) and healthy male individuals (n = 14) were evaluated using FTIR spectroscopy (range of 4000 cm(-1) - 400 cm(-1)). We focused on the areas where the results showed significant band differences and significant chemometric differences at the fingerprint region (1800 cm(-1) 900 cm(-1)), Amide I (1700 cm(-1) -1600 cm(-1)), C-H stretching band (3000 cm(-1) -2800 cm(-1)), triglyceride (Tg) levels and cholesterol esters (1800 cm(-1) -1700 cm(-1)), and total protein region (1700 cm(-1) -1350 cm(-1)). The intensity of these band areas was significantly different (p < 0.01) between OUD patients and healthy controls. Moreover, different bands on the serum spectrum of the OUD patients were explored. The results successfully specified the distinctions between OUD and the healthy controls (HCs). We compared the results with biochemical markers, such as albumin (Alb), Tg, and total cholesterol (Tc) levels of the patients, as well as the data of the healthy subjects obtained from the hospital. Additionally, we found that the Tg, Tc, and Alb levels decreased as the duration of heroin use increased based on the biochemical markers of the OUD patients. The laboratory biochemical reports and the vibrational spectroscopic analysis were correlated. The confidence of specificity, sensitivity, and accuracy was 100%, 92.85%, and 97.06% in the second derivative, respectively. Thus, we demonstrated that IR spectroscopy, multivariate data analysis, and clinical reports are consistent and correlated. Furthermore, FTIR is a simple and readily available diagnostic test that can successfully differentiate the serum samples of OUD patients from those of healthy subjects. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Blood serum; Opioid use disorder; FTIR; Biomedical compounds; PCA; LDA; RAMAN-SPECTROSCOPY; PROTEINS; FTIR